Prevalence of defined ultrasound findings of unknown significance at the second trimester fetal anomaly scan and their association with adverse pregnancy outcomes: the Welsh study of mothers and babies population‐based cohort. (20th November 2015) - Hurt, Lisa; Wright, Melissa; Dunstan, Frank; Thomas, Susan; Brook, Fiona; Morris, Susan; Tucker, David; Wills, Marilyn Ann; Davies, Colin; John, Gareth; Fone, David; Paranjothy, Shantini
Abstract: Objective: The aim of this article was to estimate the population prevalence of seven defined ultrasound findings of uncertain significance ('markers') in the second trimester and the associated risk of adverse pregnancy outcomes. Method: A prospective record‐linked cohort study of 30 078 pregnant women who had second trimester anomaly scans between July 2008 and March 2011 in Wales was conducted. Results: The prevalence of markers ranged from 43.7 per 1000 singleton pregnancies for cardiac echogenic foci [95% confidence interval (CI): 38.8, 51.1] to 0.6 for mild‐to‐moderate ventriculomegaly (95% CI: 0.3, 1.0). Isolated echogenic bowel was associated with an increased risk of congenital anomalies [risk ratio (RR) 4.54, 95% CI: 2.12, 9.73] and preterm birth (RR 2.30, 95% CI: 1.08, 4.90). Isolated pelvicalyceal dilatation was associated with an increased risk of congenital anomalies (RR 3.82, 95% CI: 2.16, 6.77). Multiple markers were associated with an increased risk of congenital anomalies (RR 5.00, 95% CI: 1.35, 18.40) and preterm birth (RR 3.38, 95% CI 1.20, 9.53). Conclusions: These data are useful for counselling families and developing clinical guidance and care pathways following the detection of markers in clinical practice, particularly the need for follow‐up scans to monitor placental function and growth in pregnancies with isolated echogenic bowel, and further investigation for multiple markers. © 2015 The Authors. Prenatal Diagnosis published by John Wiley & Sons Ltd. Abstract : What's already known about this topic? The prevalence and clinical sequelae of defined ultrasound findings of unknown significance ('markers') in pregnant women at low risk of adverse pregnancy outcomes are uncertain. Guidance on the reporting and clinical management of markers varies between and within countries. What does this study adds? This study provides population‐based estimates for the prevalence of markers in the general obstetric population, using data collected prior to referral to specialist fetal‐medicine centres. There is inter‐sonographer variation in the reporting of markers, suggesting that continuous quality assurance programmes are essential within antenatal ultrasound screening services. Isolated echogenic bowel and multiple markers are associated with an increased risk of congenital anomalies and preterm births, and isolated pelvicalyceal dilatation is associated with an increased risk of congenital anomalies. These data will be useful in counselling families and in the development of clinical guidelines and care pathways for the management of markers detected in the second trimester of pregnancy.